Prevalence of bone destruction in patients with TALAROMYCES MARNEFFEI infection: A systematic review and meta-analysis - Junhong Zhou; Deshuang Xi; Yilin Teng; Shaohui Zong; Gaofeng Zeng (International Journal of Infectious Diseases)
Objectives: This systematic review and meta-analysis aimed to evaluate the prevalence of bone destruction in patients with Talaromyces marneffei infection, examine distribution patterns of bone lesions, and assess differences between HIV-positive and HIV-negative patients. Methods: Following PRISMA guidelines, 15 studies involving 839 patients were analyzed. Random-effects meta-analysis was performed to estimate prevalence and odds ratios. Study quality was assessed using ROBINS-I. Results: The overall prevalence of bone destruction was 18% (95% CI: 10-27%). HIV-negative patients showed significantly higher odds of bone destruction (OR: 0.09, 95% CI: 0.02-0.37%). Bone lesions were widely distributed, with osseous involvement (45.7-71.4%) more prevalent than articular (7.1-66.7%). The skull, ribs, and lumbar vertebrae were commonly affected. Conclusion: Bone destruction is a significant complication in TM infection, particularly in HIV-negative patients. The diverse anatomical distribution emphasizes the need for comprehensive skeletal assessment in suspected cases.